MAKNA DENOTATIF DALAM SYAIR TARIAN â€œPOMONTEâ€ MASYARAKAT SUKU KAILI DI KOTA PALU - Kalesaran, Eirene E. P.; Kalangi, Leika Maria Victoria; Salea-Warouw, Martha (Universitas Sam Ratulangi, 2017)
This research is about the meaning contained in a song in a dance. The research reveals the denotative meaning that exists in the song